Structure and expression profile of the sucrose synthase gene family in the rubber tree: indicative of roles in stress response and sucrose utilization in the laticifers. (26th November 2013) - Xiao, Xiaohu; Tang, Chaorong; Fang, Yongjun; Yang, Meng; Zhou, Binhui; Qi, Jiyan; Zhang, Yi
<x xml:space="preserve">Abstract</x> Sucrose synthase (Sus, EC 2.4.1.13) is widely recognized as a key enzyme in sucrose metabolism in plants. However, nothing is known about this gene family in Hevea brasiliensis (para rubber tree). Here, we identified six Sus genes in H. brasiliensis that comprise the entire Sus family in this species. Analysis of the gene structure and phylogeny of the Sus genes demonstrates evolutionary conservation in the Sus families across Hevea and other plant species. The expression of Sus genes was investigated via Solexa sequencing and quantitative PCR in various tissues, at various phases of leaf development, and under abiotic stresses and ethylene treatment. The Sus genes exhibited distinct but partially redundant expression profiles. Each tissue has one abundant Sus isoform, with HbSus3, 4 and 5 being the predominant isoforms in latex (cytoplasm of rubber‐producing laticifers), bark and root, respectively. HbSus1 and 6 were barely expressed in any tissue examined. In mature leaves (source), all HbSus genes were expressed at low levels, but HbSus3 and 4 were abundantly expressed in immature leaves (sink). Low temperature and drought treatments conspicuously induced HbSus5 expression in root and leaf, suggesting a role in stress responses. HbSus2 and 3 transcripts were decreased by ethylene treatment, consistent with the reduced sucrose‐synthesizing activity of Sus enzymes in the latex in response to ethylene stimulation. Our results are beneficial to further determination of functions for the Sus genes in Hevea trees, especially roles in regulating latex regeneration.